Home for the holidays [videorecording (DVD)] - Richter, W. D.; Hunter, Holly, 1958-; Bancroft, Anne, 1931-2005; Downey, Robert, Jr., 1965- (Shout! Factory, 2017)
After losing her job, making out with her soon to be former boss and finding out that her daughter plans to spend Thanksgiving with her boyfriend, Claudia Larson faces spending the holiday with her family.